Types of upper and lower respiratory tract infection in pediatrics - Hothan, Kholoud Abdullah; Alawami, Mohammed Ali; Baothman, Eman Abdulrahman; Alghanem, Fatima Ali; Al-Haddad, Diana Mohammed; Al Daerwish, Ruqyah Ibrahim; Albetiyan, Zainab Ahmed; Alghanem, Ghadeer Ali; Bayazeed, Khulood Abdullah; Yusuf, Ghadeer Ali Al; Aljurfi, Anwar Mohammed (International Journal Of Community Medicine And Public Health, 2022)
The most prevalent diseases in infants and children, are respiratory infections including the common cold, acute rhinosinusitis, acute otitis media, flu-like illness, acute bronchitis, and pneumonia. Despite being mostly innocuous, they have a large negative impact on society and are a leading source of morbidity and mortality globally. They are further divided into two classes upper respiratory tract and lower respiratory tract infections. The purpose of this research is to review the available information about types of upper and lower respiratory tract infection in paediatrics. The common upper respiratory tract infections include acute pharyngitis which is usually self- limiting and benign and is mostly caused by viruses while inflammation of the mucosa of the paranasal sinuses and nasal cavity is a sign of acute rhinosinusitis. Common colds frequently come with uncomplicated rhinosinusitis, which does not have any clinically visible spread of the inflammation outside the paranasal sinuses and nasal cavity. A viral or bacterial infection of the middle ear causes acute otitis media. Bronchitis, bronchiolitis and pneumonia are lower respiratory infections common among children. More than one-third of children develop bronchiolitis in the first two years of life, which is the most common reason for hospitalization in the first year of life. The hospitalization rate for children has increased from 1% to 3% over the past 30 years while pneumonia is a significant contributor of morbidity and mortality among under 5 years children. Early diagnosis and prompt management can lead to better health outcomes among children.